ARE WE WITNESSING THE TWILIGHT UF THE STRATEGIC GERMAN-RUSSIAN PARTNERSHIP UNDER ANGELA MERKEL? - KOSZEL, Bogdan (Przegląd Strategiczny, 2018)
The author of this paper analyzes the policy of strategic partnership between Germany and Russia, especially in the field of the economy, which originated after the reunification of Germany in 1990. He stresses that it was the government of Angela Merkel after 2005 that began to emphasize the authoritarian rule of President Vladimir Putin and human rights breaches in Russia. Nevertheless, economic cooperation continued under the pressure from business circles. The author’s main hypothesis is that it was only Russia’s aggression towards Ukraine that undermined German-Russian collaboration, which is no longer given priority. Germany is the foremost advocate of the EU’s maintaining its sanctions against Russia. Angela Merkel’s third and fourth governments have tried to ‘Europeanize’ Germany’s policy towards the Russian Federation to a greater extent. Both Germany and the EU need Russia as a strategic partner to resolve problems in the Middle East and combat international terrorism. Russia is also a significant supplier of strategic resources to Germany and the EU. This paper employs the descriptive research method, the method of source analysis and decision-making analysis.